Hypercholesterolemia and Ecto‐enzymes of Purinergic System: Effects of Paullinia cupana. (30th October 2015) - Ruchel, J. B.; Rezer, J. F. P.; Thorstenberg, M. L.; dos Santos, C. B.; Cabral, F. L.; Lopes, S. T. A.; da Silva, C. B.; Machado, A. K.; da Cruz, I. B. M.; Schetinger, M. R. C.; Gonçalves, J. F.; Leal, D. B. R.
Abstract : Hypercholesterolemia is a metabolic disorder characterized by high levels of low‐density lipoprotein and blood cholesterol, causing inflammatory lesion. Purinergic signaling modulates the inflammatory and immune responses through adenine nucleotides and nucleoside. Guaraná has hypocholesterolemic and antiinflammatory properties. Considering that there are few studies demonstrating the effects of guaraná powder on the metabolism of adenine nucleotides, we investigated its effects on the activity of ecto‐nucleoside triphosphate diphosphohydrolase (E‐NTPDase) and ecto‐adenosine deaminase activity in lymphocytes of rats with diet‐induced hypercholesterolemia. The rats were divided into hypercholesterolemic and normal diet groups. Each group was subdivided by treatment: saline, guaraná powder 12.5, 25, or 50 mg/kg/day and caffeine concentration equivalent to highest dose of guaraná, fed orally for 30 days. An increase in adenosine triphosphate hydrolysis was observed in the lymphocytes of rats with hypercholesterolemia and treated with 25 or 50 mg/kg/day when compared with the other groups. The hypercholesterolemic group treated with the highest concentration of guaraná powder showed decreased ecto‐adenosine deaminase activity compared with the normal diet groups. Guaraná was able to reduce the total cholesterol and low‐density lipoprotein cholesterol to basal levels in hypercholesterolemic rats. High concentrations of guaraná associated with a hypercholesterolemic diet are likely to have contributed to the reduction of the inflammatory process. Copyright © 2015 John Wiley & Sons, Ltd.